MANAGEMENT OF PHACOMORFIC GLAUCOMA WITH FILTRATION SURGERY: Poster Presentation - Case Report - Resident - Nabdakh, Alifvia; Subsp GL, Dr. dr. Fidalia Sp.M (K); Sari Sp.M (K) Subsp GL, dr. Prima Maya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Phacomorphic glaucoma is form of glaucoma that occurs due to a swollen cataractous lens. Filtration surgery in one of the option for managing phacomorphic glaucoma. This surgical approach can be effective in controlling intraocular pressure and preventing further damage to the optic nerve Case Illustration : A 53 yo female complaints of progressively blurry vision in her left eye. The LE visual acuity 6/30 and IOP 25,9. The gonioscopy showed a close-angle impression in all quadrants, VH gr 1. Also thereis increase lens opacity , Posterior segment examination revealed ]cup/disc ratio of 0.9 and cupping. The patient was diagnosed with secondary glaucoma (phacomorphic). Filtration surgery of trabeculectomy + 5-FU is performed Discussion : The patient was treated with trabeculectomy and 5-FU, resulting in IOP to 17 mmHg. The surgical procedure is aim to reduce intraocular pressure to create a channel and reservoir for blocked aqueous humor, resulting in decreased IOP and stopping the damage process to the optic nerve. This approach aims to increase the success rate and reduce the likelihood of complications during the operation. Conclusion : The limportance of prompt management of phacomorphic glaucoma to prevent permanent vision loss, and the use of trabeculectomy as an effective surgical approach in controlling intraocular pressure and preventing further damage to the optic. Cataract extraction surgery remains the definitive therapy for phacomorphic glaucoma cases, and this approach should be considered in the future management of the patient